The Lost “Linant de Bellefonds Stela” of the Chief-Treasurer Maya and its Hymn and Prayer to the Sun-God - Pasquali, Stéphane (Zeitschrift für ägyptische Sprache und Altertumskunde, 2024)
Publication of a new stela of the Chief-Treasurer Maya (time of Tutankhamun-Horemheb) with a long hymn addressed to the rising sun. The closest versions of the text are those of pNakht (London BM EA 10471, 21), the London stela of Horemheb (BM EA 551), and the pyramidion of Amenhotep Huy in the Rijksmuseum van Oudheden, Leiden (AM 6-b) – one sequence about the sun rays and the Haunebut (line 5) is original in view of the available documentation. The stela (now lost) which was in the possession of Linant de Bellefonds in 1850, is only known thanks to a handwritten copy by Auguste Mariette. There can be no doubt that it comes from the tomb of Maya at Saqqara.